Genus Leptoiulus Verhoeff, 1894 new to the fauna of the Asian part of Russia, with description of a new species from the Altai and its comparison with the European Leptoiulus trilineatus (C.L. Koch, 1847) (Diplopoda, Julida, Julidae) - Mikhaljova, Elena V.; Nefediev, Pavel S.; Nefedieva, Julia S.; Dyachkov, Yuri V. (Zootaxa, 2015)
The diplopod genus Leptoiulus Verhoeff, 1894 is new to the fauna of the Asian part of Russia, due to the discovery of        L. tigirek sp. nov. from the south-western part of the Altai Province, Siberia. A description of the new species and information on its habitats, numbers and locomotor activity as well as comparison with the European Leptoiulus trilineatus (C.L. Koch, 1847) are presented.